Tafsiran Ayat-Ayat Politik dalam Al-Quran Menurut Ibnu Kathir: Suatu Tin-Jauan Konteks Malaysia - Abdulloh Salaeh; Hayati Hussin; Syed Najihuddin Syed Hassan; Norullisza Khosim; Ahmad Kamel Mohamed; Amran Abdul Halim (Penerbit USIM, 2025)
International Conference of Quran as Foundation of Civilization (SWAT 2025) : Maqasid al-Quran and the Madani Vision: A Guiding Light for Regional Serenity and Global Unity Organized by : Faculty of Quranic and Sunnah Studies, in collaboration with Nasyrul Quran and Daffodil International University, Bangladesh. Date:12-13 November 2025